CircRNA SEC24A promotes osteoarthritis through miR-107-5p/CASP3 axis - Tuerxunjiang Dadihanc; Yong Zhang; Guo-Qing Li; Hai-Kang Zhou; Jingyong Huang; Xue Zhang; Zhi-Qiang Li; Hai-Rong Ma (Regenerative Therapy)
Background: Osteoarthritis (OA) is the most frequently diagnosed chronic joint disease. CircSEC24A is significantly elevated in OA chondrocytes upon IL-1β stimulation. However, its biological function in OA is still not fully understood. Methods: The circRNAs-miRNA-mRNA network was predicted by bioinformatics analysis. An in vitro OA chondrocytes model was established by IL-1β stimulation. The expression of circSEC24A, miR-107-5p, CASP3, apoptosis-related molecules and extracellular matrix (ECM) components were detected by Western blot and qRT-PCR. MTT assay and Annexin V/PI staining were employed to monitor cell viability and apoptosis, respectively. The interaction between circSEC24A and miR-107-5p, as well as the binding between miR-107-5p and CASP3 3’ UTR were detected by luciferase reporter and RIP assays. Cytokine secretion was monitored by ELISA assay. The role of circSEC24A was also explored in anterior cruciate ligament transection (ACLT) rat models. Results: CircSEC24A and CASP3 were increased, but miR-107-5p was decreased in rat OA cartilage tissues and OA chondrocytes. CircSEC24A acted as a sponge of miR-107-5p. Knockdown of circSEC24A promoted chondrocyte proliferation, but suppressed chondrocyte apoptosis, ECM degradation and inflammation via sponging miR-107-5p. CASP3 was identified as a miR-107-5p target gene. MiR-107-5p mimics protected against OA progression via targeting CASP3. Silencing of circSEC24A alleviated OA progression in ACLT model. Conclusion: CircSEC24A promotes OA progression through miR-107-5p/CASP3 axis.